TQM and Organizational Performance: A Mediating Role of Strategies for Continues Improvement: An Evidence from Coffee Cooperative in Ethiopia - Megersa, Gezew; Chalchisa A (RADINKA JOURNAL OF SCIENCE AND SYSTEMATIC LITERATURE REVIEW, 2024)
The purpose of this study was to examine total quality management practices and organization performance with the mediating role of strategies for continuous improvement. Besides that, the study aimed to bridge a gap in the literature and knowledge of total quality management practices and organization performance with strategies for continuous improvement. The study employed an explanatory and descriptive research design and used a mixed approach. A survey was conducted using self-administered and structured, closed-ended questionnaires that were distributed to respondents. Descriptive statistics and correlation statistical tools were used to examine the relationship between total quality management ingredients and organizational performance, and multiple regression analysis was used to measure the effects of independent variables on the dependent variable. The study adopted a probability sampling technique, specifically a simple random sampling technique. The data was analyzed using Amos in SPSS. The correlation analysis was performed to identify the direction and strength of the relationship between variables, whereas the SEM (structural equation model) analysis was used to describe the causal effect between and among dependent and independent variables under investigation. Concerning SEM analysis, the study found total quality management and strategies had positive and significant effects on organizational performance. It is recommended that firms continually implement TQM and use strategies properly to improve performance.